Coarse root distribution of a semi‐arid oak savanna estimated with ground penetrating radar. Issue 1 (11th February 2013) - Raz‐Yaseef, Naama; Koteen, Laura; Baldocchi, Dennis D.
Abstract : [1] The binary nature of Northern California's ecohydrology, in which water is either abundantly available or scarce, should be reflected in the root architecture of the native blue oak. Our objective was to quantify carbon storage and understand how the form of the root system facilitates ecosystem functioning despite the asynchrony between winter water availability, spring leaf growth, and dry‐summer canopy maintenance. To do this, we surveyed coarse root distribution with a ground penetrating radar (GPR), due to its advantages in covering large areas rapidly and non‐destructively. We calibrated root biomass detected by GPR against roots excavated from a number of small pits. Based on a survey of six tree configurations (varying in age, size, and clumping), we found that coarse roots occupy the full soil profile and that coarse root biomass of old large trees reached a peak directly above the bedrock. As opposed to other semi‐arid regions, where trees often develop extensive shallow lateral coarse roots to exploit the entire wet‐soil medium, we found that root density decreased with distance from the bole, and dropped sharply beyond a distance of 2 m. We upscaled tree root biomass to stand scale (2.8 ± 0.4 kg m −2 ) based on lidar analysis of the relative abundance of each tree configuration. We argue that this deep and narrow root structure reflects the ecohydrology of oaks in this ecosystem. An extensive lateral root system would not be beneficial during the growing season, when water is sufficiently abundant, nor during summer, when soil water is highly limited. Key Points: Coarse roots in semi‐arid savanna surveyed to see how form follows function Ground penetrating radar successfully determined coarse root biomass and spatial variability Root structure explains the incongruity of tree growth with water availability